Method to investigate and plan the application of low temperature district heating to existing hydraulic radiator systems in existing buildings. (15th October 2016) - Tunzi, Michele; Østergaard, Dorte Skaarup; Svendsen, Svend; Boukhanouf, Rabah; Cooper, Edward
Abstract: This study presents a method to adapt existing hydronic systems in buildings to take advantage of low temperature district heating (LTDH). Plate radiators connected to double string heating circuits were considered in an optimization procedure, based on supply and return temperatures, to obtain the required logarithmic mean temperature difference (LMTD) for a low temperature heating system. The results of the analysis are presented as the average reduction of LMTD over the heating season compared to the base case design conditions. Two scenarios were investigated based on the assumption of a likely cost reduction in the end users' energy bills of 1% for each 1 °C reduction of return and average supply and return temperatures. The results showed possible discounts of 14% and 16% respectively, due to more efficient operation of the radiators. These were achieved without any intervention in the thermal envelope or to the heating systems, through simply adjusting the temperatures according to demand and properly controlling the plate radiators with thermostatic radiator valves (TRVs). Highlights: Application of low operating temperatures to existing hydraulic radiators. Method to investigate and plan the connection of existing buildings to low temperature district heating. Investigation to calculate performance of hydraulic radiator element. Method to optimize supply and return temperatures in low temperature district heating system.